NERVOUS INTEGRATION OF VOLUNTARY MOVEMENT - Dănoiu Mircea; Manuela Băcănoiu; Zăvăleanu Mihaela (Universitaria Publishing House, Craiova, 2017)
Designed as a true cyber scheme, execution of volitional movements is a synergistic combination of different sensory and motor factors which is reflected in muscle contractions, adequate control over the intensity, hierarchy, chronology and spatial location of body or different parts of the body. All body biomechanical activities results from a double command which simultaneously produces the contraction of two muscle groups with antagonistic action. Those are the flexors and extensors. The first group contract and produce the desired movement, the second group provides relaxation and modulates movement. The movement would lose precision and safety, also can occur excessive contractions without this synchronization between the muscles agonists and antagonists. Voluntary movement involves a complex process of coordinated steps required not only for initiation, but also for the cessation of muscle contraction, and the intimate nature of the processes in which volitional consciousness is capable of expressing itself in terms of movement remains incomprehensible. In the rehabilitation and sport, the accuracy of the voluntary movements is crucial. The learning and repetition for learning of one motion require a complex image of the temporal and spatial succession and nervous integration of the elementary movements that must be executed in a special order to achieve the desired action. Those succesion are the base of rehabilitation and sport and must be well understude in order to achieve the ideal voluntary movement.